PENGARUH PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA RILL PADA PERUSAHAAN DENGAN KUALITAS AUDIT YANG BERBEDA - Ramadanty, Diva Arsitya; Saragi, Nanda Putra; Soetardjo, Mulyadi Noto (Universitas Pelita Harapan, 2024)
This study aims to test and obtain empirical evidence regarding the effect of tax planning on real earnings management, as well as the effect of audit quality and the Covid -19 pandemic on the relationship between tax planning and real earnings management. The independent variable used in this study is tax planning and the dependent variable used is real earnings management. This study also uses audit quality and the Covid-19 pandemic as moderating variables. The research data is secondary data in the form of financial reports taken through S&P Capital IQ. The research sample used is the financial statements of companies in consumer staples sector listed on the Indonesia Stock Exchange (IDX) during 2018 - 2022, with final sample 316 data from 85 companies. The purposive sampling method was used as a sample collection technique and the data was analyzed using multiple regression methods with IMB SPSS 27 software. The results of this study indicate that tax planning has a negative effect on real earnings management, audit quality weakens the relationship between tax planning and real earnings management, and the Covid-19 pandemic has no effect on the relationship between tax planning and real earnings management. The implication of this research is to increase knowledge about the effect of tax planning on real earnings management and the effect of audit quality on the relationship between them.